Amino‐Functionalized Metal–Organic Frameworks Featuring Ultra‐Strong Ethane Nano‐Traps for Efficient C2H6/C2H4 Separation - Zhang, Li‐Ping; Guan, Guo‐Wei; Li, Yi‐Tao; Liu, Hao‐Ran; Zheng, Su‐Tao; Jiang, Yu; Bai, Rui; Yang, Qing‐Yuan (Small (Weinheim an der Bergstrasse, Germany), 2024)
Developing high‐performance porous materials to separate ethane from ethylene is an important but challenging task in the chemical industry, given their similar sizes and physicochemical properties. Herein, a new type of ultra‐strong C2H6 nano‐trap, CuIn(3‐ain)4 is presented, which utilizes multiple guest‐host interactions to efficiently capture C2H6 molecules and separate mixtures of C2H6 and C2H4. The ultra‐strong C2H6 nano‐trap exhibits the high C2H6 (2.38 mmol g−1) uptake at 6.25 kPa and 298 K and demonstrates a remarkable selectivity of 3.42 for C2H6/C2H4 (10:90). Additionally, equimolar C2H6/C2H4 exhibited a superior high separation potential ∆Q (2286 mmol L−1) at 298 K. Kinetic adsorption tests demonstrated that CuIn(3‐ain)4 has a high adsorption rate for C2H6, establishing it as a new benchmark material for the capture of C2H6 and the separation of C2H6/C2H4. Notably, this exceptional performance is maintained even at a higher temperature of 333 K, a phenomenon not observed before. Theoretical simulations and single‐crystal X‐ray diffraction provide critical insights into how selective adsorption properties can be tuned by manipulating pore dimensions and geometry. The excellent separation performance of CuIn(3‐ain)4 has been confirmed through breakthrough experiments for C2H6/C2H4 gas mixtures. This study successfully synthesized a new benchmark ethane‐selective adsorbent material, CuIn(3‐ain)4, by incorporating an amino group into the ligand. Due to its outstanding separation efficiency, durability, and cost‐effectiveness, CuIn(3‐ain)4 becomes a viable option for industrial applications.